Gambaran Determinan Resiliensi pada Remaja yang Mengalami Kehamilan di Luar Nikah: Studi Kasus - Andini Damayanti; Qothrun Nada; Erizza Farizan Adani; Eldatia Utari Putri; Endang Retno Surjaningrum (Humanitas (Jurnal Psikologi), 2022)
Adolescents who experienced pregnancy out of wedlock are prone to experience negative social and physical impacts which can lead to abortion, depression and anxiety. However, not every adolescent who are pregnant out of wedlock are affected, due to resiliency. Therefore, researchers wants to know more about determinants who affected resiliency on adolescents who are pregnant out of wedlock. This research is a qualitative research with case study method, collected by semi-structured interviews and supported by documents from NGO.. Data were analyzed by thematic analysis according to the adolescent resilience model of Rew and Horner (2003). The results show that adolescents have protective and risk factors that interact so the factors are able to shape resilience and adaptive behavior.